Assessment of the quality of interdisciplinary communication (CritCom): evaluation and refinement of a center summary report - Counts, Lara; Rivera, Jocelyn; Wiphatphumiprates, Parima; Puerto-Torres, Maria; Prewitt, Kim; Luke, Douglas A.; Graetz, Dylan E.; Malone, Sara; Agulnik, Asya (Frontiers in Oncology, 2024)
Communication failures among clinicians in the ICU (intensive care unit) often lead to worse patient outcomes. CritCom is a bilingual (English and Spanish) tool to evaluate the quality of interdisciplinary communication around patient deterioration for pediatric oncology patients. Use of reports, such as the CritCom report, as dissemination methods lead to quicker knowledge translation and implementation of research findings into policy. Nurses and Physicians at participating centers who care for patients at risk of deterioration completed the CritCom survey and center-specific reports were generated to communicate CritCom results. Focus groups were conducted with clinicians receiving CritCom reports in both English and Spanish to evaluate report clarity and usability. Participants found the reports to be useful and described the writing and design as clear and specific. Participants provided feedback to improve report design and requested actionable steps to improve communication at their center. Feedback illustrated that the report was easy to interpret and a useful way to disseminate information. Participants noted the utility of the report, illustrating that the use of reports can be a useful method to disseminate research findings back to participants in a way that is applicable to the local context. Communicating research findings through reports can minimize the significant time lag in knowledge translation and provide participants with actionable steps to implement in their setting.